Pioneer Prophetess : Jemima Wilkinson, the Publick Universal Friend - Wisbey, Herbert A. (Herbert Andrew), 1919- (Book collections on Project MUSE., 1964)
At the age of twenty-four, the Rhode Island Quaker Jemima Wilkinson (1752-1819) recovered from a bout of fever with the pronouncement that she had been directed by a vision to preach to a "dying and sinful world." Announcing that Jemima had died and that her body now housed a new spirit, the Publick Universal Friend, this remarkably charismatic-and notably scandal-plagued-woman gathered several hundred followers and settled to the west of Seneca Lake. Although the religious community she founded on a framework of abstinence and friendship did not long survive her, Wilkinson remains a figure of fascination and mystery to this day. Herbert A. Wisbey Jr.'s 1964 biography is the authoritative account of her life, times, and ideals